Effect of Digestible Threonine Level of Diet on Productive Performance, Commercial Egg Grading and Egg Quality of 55- to 61-Week-Old Laying Hens - Antonio, Callejo Ramos; Andrea, Luciana dos Santos; Nuria, Nicodemus Martin; Maria, Jesus Villamide Diaz; Ángela, Gutiérrez del Álamo; Carlos, Isidro Buxade Carbó; Alessandro, Borges Amorim; Mayra, Anton Dib Saleh (Journal of Veterinary Healthcare, 2017)
The aim of this study was to establish the digestible threonine (dig. Thr) requirements and the ideal proportion between Thr and Lys for Isa Brown laying hens on productive traits and egg quality characteristics from 55- to 58- and 59- to 61 weeks of age. Increased levels of L-Thr were added to a basal diet that contained 3.7 g/kg of dig. Thr. Therefore, diets containing 3.7, 4.0, 4.3, 4.6, 4.9 and 5.2 g/kg of dig. Thr and a relation between Thr and Lys of 0.58, 0.63, 0.67, 0.72, 0.77 and 0.81, respectively were provided to laying hens. A total of 216 hens were distributed in a randomized design among the 6 experimental diets. There were 9 replicates per treatment, and 4 birds per replicate. Data were analyzed by repeated measures analysis using the MIXED procedure of SAS. The main effects (dig. Thr level and experimental period) and their interaction were studied. Neither the dig. Thr level nor the experimental period had effect on performance traits and egg quality. Also, commercial egg grading was not influenced by period. However, there was a quadratic effect (P<0.001) of dig. Thr level within each scale egg weight. In conclusion, diets containing more than 3.7 g/kg of dig. Thr do not improve laying hens productivity at 55- to 61-week-old.
Keywords: amino acid; egg quality; hatch; poultry; productivity